Acute effects of exercise intensity on butyrylcholinesterase and ghrelin in young men: A randomized controlled study - Yibin Li; Yusei Tataka; Miki Sakazaki; Kayoko Kamemoto; Chihiro Nagayama; Yoshie Yoshikawa; Yoshiki Yamada; Masashi Miyashita (Elsevier, 2024)
Background/objectives: Butyrylcholinesterase (BChE), a liver-derived enzyme that hydrolyzes acylated ghrelin to des-acylated ghrelin, may trigger a potential mechanism responsible for the acute exercise-induced suppression of acylated ghrelin. However, studies examining the effects of an acute bout of high-intensity exercise on BChE and acylated ghrelin have yielded inconsistent findings. This study aimed to examine the acute effects of exercise intensity on BChE, acylated ghrelin and des-acylated ghrelin concentrations in humans. Methods: Fifteen young men (aged 22.7 ± 1.8 years, mean ± standard deviation) completed three, half-day laboratory-based trials (i.e., high-intensity exercise, low-intensity exercise and control), in a random order. In the exercise trials, the participants ran for 60 min (from 09:30 to 10:30) at a speed eliciting 70 % (high-intensity) or 40 % (low-intensity) of their maximum oxygen uptake and then rested for 90 min. In the control trial, participants sat on a chair for the entire trial (from 09:30 to 12:00). Venous blood samples were collected at 09:30, 10:00, 10:30, 11:00, 11:30 and 12:00. Results: The BChE concentration was not altered over time among the three trials. Total acylated and des-acylated ghrelin area under the curve during the first 60 min (i.e., from 0 min to 60 min) of the main trial were lower in the high-intensity exercise trial than in the control (acylated ghrelin, mean difference: 62.6 pg/mL, p < 0.001; des-acylated ghrelin, mean difference: 31.4 pg/mL, p = 0.035) and the low-intensity exercise trial (acylated ghrelin, mean difference: 87.7 pg/mL, p < 0.001; des-acylated ghrelin, mean difference: 43.0 pg/mL, p = 0.042). Conclusion: The findings suggest that BChE may not be involved in the modulation of ghrelin even though lowered acylated ghrelin concentration was observed after high-intensity exercise.